Dysphoria is a risk factor for depression in medically ill older people. (2nd February 2016) - Mukaetova‐Ladinska, E. B.; Steel, M.; Coppock, M.; Cosker, G.; James, P.; Scully, A.; McNally, R. J.
Abstract : Objectives: Depression in older people is commonly under diagnosed and is associated with increased morbidity and mortality. Because older people currently occupy 65% of acute hospital beds, it is crucial for them to be properly assessed for depression to optimise their medical care. The aim of this study was to identify potential risk factors for depression in the medically ill in order to improve their inpatient care. Methods: This was a 2‐year observational study of consequent referrals to the Newcastle Liaison Team for Older Adults. Out of a total number of 1586 referred patients, 1197 were included in the final analysis of data. Information about their age, main medical history, cognitive impairment and use of antidepressants was collected. All subjects were screened for dementia, depression and delirium. Proportions were compared using the chi‐squared test. Clinical depression as a binary variable was modelled using logistic regression. Results: Higher risk for depression was associated with pain (odds ratio (OR) = 1.76; p = 0.033) and a previous history of depression (OR = 2.22; p < 0.001). Cognitive impairment (OR = 0.44, p < 0.001) and delirium (OR = 0.49; p < 0.001) decreased the likelihood for having depression. Subjective feelings of emptiness, being unhappy and depressed alone ( R 2 = 37.4%) and cognitive impairment ( R 2 = 39.5%) were the best multivariable model to explain depression in medically ill people. Conclusion: Dysphoric mood results in depression in older people with medical health problems. Copyright © 2016 John Wiley & Sons, Ltd.